Towards participatory urban planning: insights from citizens. Results of a public questionnaire on climate change and its local effects in Parma - De Noia, Ilaria; Caselli, Barbara; Kemperman, Astrid; Rossetti, Silvia; van der Waerden, Peter (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Citizen involvement in urban transition processes has been gaining recognition within the scientific literature and urban transformation initiatives, highlighting the significance of meaningful citizen participation in promoting healthier and more resilient cities. Co-design and co-planning, in both top-down and bottom-up urban transformation processes, allow stakeholders to collaborate in defining the future of cities in a climate change adaptation framework that encompasses interventions such as soil desealing. In this framework, public questionnaires have emerged as valuable instruments to solicit citizens' insights into participatory processes, as an aid to orient urban planning and transformation scenarios towards their needs and vulnerabilities. After tracing the outline of a local bottom-up project (named “Green in Parma”), this contribution will present and discuss the outcomes of a questionnaire that investigated the perception of the citizens of Parma regarding climate change and its local effects. Univariate and bivariate analyses, including Chi-square tests and factor analyses, were conducted on data collected from a sample of 1,352 participants. The findings provided insights linked to the city and to the neighbourhoods, allowing to localise the quantitative data. The results were enriched with qualitative associations with the neighbourhoods socio-environmental characteristics, fostering the envisioning of climate change adaptation strategies. The analyses reveal the potential of questionnaires and citizens’ involvement in shaping urban planning scenarios, acknowledging the citizens’ role as bearers of knowledge and active stakeholders.